Analisis Multi Akad (Al-Uqud al-Murakkabah) terhadap Penggabungan Akad Musyarakah Mutanaqisah dan Ijarah pada KPR Syariah - Cucu Juhana; Encum Sumirah (MUAMALAH: Journal of Islamic Economics and Business Law, 2026)
The Islamic banking industry in Indonesia is currently shifting its trend in Home Ownership Financing (KPR) products from the dominance of Murabahah contracts to the Musyarakah Mutanaqisah (MMQ) scheme, which is considered to better reflect the principle of equity-based financing. However, the implementation of MMQ presents juridical complexities as its structure is not a single contract, but rather an Al-Uqud al-Murakkabah (hybrid contract) construction combining Syirkah, Ijarah, and Bai’ into one scheme. This amalgamation triggers polemics regarding potential violations of the prohibition of Bai'atain fi Bai'ah (two transactions in one contract) and the existence of ta'alluq (interdependence) elements that could undermine the contract's validity. Another crucial issue is the potential for gharar (uncertainty) in fluctuating rental pricing and the risk of confusion between rental payments and principal repayment, leading to Riba Fadhl. This study aims to analyze the legal standing of contract amalgamation in MMQ and formulate sharia parameters distinguishing valid innovation from invalid manipulation. This is a juridical-normative research employing conceptual and comparative approaches. The analysis juxtaposes classical fiqh literature specifically Ibn Taimiyah's views on freedom of contract with the positive regulation of DSN-MUI Fatwa No. 73/DSN-MUI/XI/2008. The results conclude that the MMQ construction is categorized as Al-Uqud al-Murakkabah al-Jaizah (permissible). This validity stands because each constituent contract fulfills its pillars and conditions independently and shares harmonious objectives (muqtadha al-aqd). The ta'alluq issue is resolved through the Wa’ad (unilateral promise) mechanism, which bridges the separation between the lease contract and the purchase commitment, thereby preserving the principle of luzum. Nevertheless, this study recommends that Islamic banks reform transparency by explicitly separating the ujrah (benefit cost) portion and the buyu' (ownership transfer) portion in the customer's installment table. This transparency is absolute to ensure MMQ functions as a truly sharia-compliant asset ownership instrument, not merely a replication of conventional loan interest payments.